How do you find the derivative of inverse trig functions #y= arctan(x^2-1)^(1/2) + arc csc(x)# when x>1?

Answer 1

#y^' = 0#

Assuming the equation was meant to be read as

#y = arctan(sqrt(x^2-1)) + arc csc(x)#

We can say the derivative will be the sum of the two other derivatives

#u = arctan(sqrt(x^2-1))# #v = arc csc(x)#
#v# will be easier to differentiate, know, knowing that
#csc(arc csc(x)) = x#

We differentiate both sides and use the chain rule, so

#1 = csc^'(arc csc(x))*arc csc^'(x)# #1/csc^'(arc csc(x)) = arc csc^'(x)#
We know that the derivative of the cossecant is #-csc(x)cot(x)#, so, in other words
#1/(-csc(arc csc(x))cot(arc csc(x))) = arc csc^'(x)#

Since they're both rational functions we can bring them up to the numerator

#-tan(arc csc(x))/x = arc csc^'(x)#
Using the pythagorean identity #1 + cot^2(theta) = csc^2(theta)# we have
#1 + 1/(tan^2(arc csc(x))) = x^2#
#1/(tan^2(arc csc(x))) = x^2 - 1#
#tan(arc csc(x)) = 1/sqrt(x^2 - 1)# so
#arc csc^'(x) = -1/(xsqrt(x^2-1)) #
(There are authors that say it like this, there are people that have that leading x as #|x|#, considering we're working with #x > 1#, the absolute value bars aren't needed regardless of your philosophy if they should be there or not).
Now, we do #u = arctan(sqrt(x^2-1))#, for the sake of brevity, I'll skip the proof of the arctan's derivative, as the process is much like the one used for the arccsc, except it'd involve the #tan^2(theta) + 1 = sec^2(theta)# identity.

So we have

#u = arctan(sqrt(x^2-1))# #u^' = arctan^'(sqrt(x^2-1))*sqrt((x^2-1))^'*2x#

It's important to remember we need to apply the chain rule twice here.

#u^' = 1/(1+(sqrt(x^2-1))^2)*1/(2sqrt(x^2-1))*2x# #u^' = 1/(1+x^2-1)*1/(2sqrt(x^2-1))*2x# #u^' = 1/x^2*1/(2sqrt(x^2-1))*2x# #u^' = 1/(xsqrt(x^2-1))#

Summing them up we have

#y^' = 1/(xsqrt(x^2-1)) - 1/(xsqrt(x^2-1)) = 0#
Which makes sense if you look at the graph for #x > 0#. For smaller values the absolute value probably would have mattered and would have made the derivative non-zero.
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

To find the derivative of the given function, we apply the chain rule and the derivative formulas for inverse trigonometric functions:

  1. For ( y = \arctan((x^2 - 1)^{1/2}) ):

    • Let ( u = (x^2 - 1)^{1/2} ).
    • Then, ( y = \arctan(u) ).
    • Applying the chain rule, the derivative is ( \frac{dy}{dx} = \frac{1}{1 + u^2} \cdot \frac{du}{dx} ).
    • Now, find ( \frac{du}{dx} ) using the power rule: ( \frac{du}{dx} = \frac{1}{2}(x^2 - 1)^{-1/2} \cdot 2x = \frac{x}{(x^2 - 1)^{1/2}} ).
    • Substitute back into the derivative: ( \frac{dy}{dx} = \frac{1}{1 + u^2} \cdot \frac{x}{(x^2 - 1)^{1/2}} = \frac{x}{(x^2 - 1) + x^2} = \frac{x}{2x^2 - 1} ).
  2. For ( y = \text{arccsc}(x) ):

    • Recall that ( \text{arccsc}(x) = \arcsin\left(\frac{1}{x}\right) ).
    • Applying the derivative of ( \arcsin ), we have ( \frac{d}{dx}(\arcsin(u)) = \frac{1}{\sqrt{1 - u^2}} \cdot \frac{du}{dx} ).
    • So, ( \frac{dy}{dx} = \frac{1}{\sqrt{1 - (1/x)^2}} \cdot \left(-\frac{1}{x^2}\right) = -\frac{1}{|x|\sqrt{x^2 - 1}} ).

Therefore, the derivative of the given function is:

[ \frac{dy}{dx} = \frac{x}{2x^2 - 1} - \frac{1}{|x|\sqrt{x^2 - 1}} ]

for ( x > 1 ).

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7